Corporate governance and the venture capital process in emerging markets: evidence from Poland - Klonowski, Dariusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
This article examines the perceived corporate governance problems within the venture capital investment process. Evidence is provided to demonstrate that venture capitalists in Poland address their corporate governance concerns in a sequential or hierarchical manner. Venture capitalists first focus on addressing issues related to financial control and accountability (during the screening stage). Secondly, they address conflict of interest concerns (during the deal agreement stage). Once these two major corporate governance concerns are addressed, venture capitalists move to focus on corporate governance enhancement (during the monitoring stage), and, finally, on value maximization (during the divestment stage). 99 questionnaires were sent out to investment officers from thirty three venture capital funds operating in Poland, yielding the response rate of 56 percent
Argumenta Oeconomica, 2008, No 2 (21), s. 27-50
Keywords: venture; capital; corporate; governance; Poland; ład korporacyjny; rynki wschodzące